Cholinesterase inhibitors in patients with diabetes mellitus and dementia: an open-cohort study of ~23 000 patients from the Swedish Dementia Registry. Issue 1 (15th January 2020) - Secnik, Juraj; Schwertner, Emilia; Alvarsson, Michael; Hammar, Niklas; Fastbom, Johan; Winblad, Bengt; Garcia-Ptacek, Sara; Religa, Dorota; Eriksdotter, Maria
Abstract : Objective: Cholinesterase inhibitors (ChEIs) and memantine are the only approved pharmacological treatments for Alzheimer's disease (AD). Recent literature suggests reductions in cardiovascular burden and risk of stroke in ChEI users. However, the clinical effectiveness of these drugs in patients with diabetes mellitus (DM) and dementia has not been evaluated. Research design and methods: We conducted a registry-based open-cohort study of 22 660 patients diagnosed with AD and mixed-pathology dementia registered in the Swedish Dementia Registry until December 2015. Information on drug use, comorbidity and mortality was extracted using the linkage with the National Patient Registry, the Prescribed Drug Registry and the Cause of Death Registry. In total, 3176 (14%) patients with DM and 19 484 patients without DM were identified. Propensity-score matching, Cox-regression and competing-risk regression models were applied to produce HRs with 95% CIs for differences in all-cause, cardiovascular and diabetes-related mortality rates in ChEI users and non-users. Results: After matching the ChEI use in patients with DM was associated with 24% all-cause mortality reduction (HR 0.76 (95% CI 0.67 to 0.86)), compared with 20% reduction (0.80 (0.75 to 0.84)) in non-DM users. Donepezil and galantamine use were associated with a reduced mortality in both patients with DM (0.84 (0.74 to 0.96); 0.80 (0.66 to 0.97)) and patients without DM (0.85 (0.80 to 0.90); 0.93 (0.86 to 0.99)). Donepezil was further associated with reduction in cardiovascular mortality, however only in patients without DM (0.84 (0.75 to 0.94)). Rivastigmine lowered mortality only in the whole-cohort analysis and in patients without DM (0.82 (0.75 to 0.89)). Moreover, ChEI use was associated with 48% reduction in diabetes-related mortality (HR 0.52 (0.32 to 0.87)) in the whole-cohort analysis. Last, low and high doses were associated with similar benefit. Conclusions: We found reductions in mortality in patients with DM and AD or mixed-pathology dementia treated with ChEIs, specifically donepezil and galantamine were associated with largest benefit. Future studies should evaluate whether ChEIs help maintain self-management of diabetes in patients with dementia.